Securitisation: a crucial strategic tool for banking sector. Case study of Royal Bank of Scotland and ABN AMRO - Gaba, Sergei (2009)
An importance of securitisation as financial tool increases every year. Many companies declare securitisation as their principal funding and earnings stream. Especially today, when credit markets are highly developed, securitisation became the next mechanism to push this development further. The idea of this dissertation is to explain the topicality of securitisation. For this reason an extensive literature review is given, where huge importance is given to types of securitisation and main advantages and disadvantages associated with it. Special purpose vehicle and credit enhancements are also properly examined for better comprehension of main characteristics of securitisation. Two case studies of Royal Bank of Scotland and Dutch bank ABN AMRO are accurately analysed and critically evaluated. This paper also benefits from primary research which is conducted in UK banking sector. For statistical treatment of data SPSS program is used. Finally, suggestions are given in conclusion for future research.